2019
DOI: 10.3389/fncir.2019.00067
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Corticothalamic Layer 6 Cells Decreases Angular Tuning in Mouse Barrel Cortex

Abstract: In the mouse whisker system, the contribution of L6 corticothalamic cells (L6 CT) to cortical and thalamic processing of the whisker deflection direction was investigated. A genetically defined population of L6 CT cells project to infragranular GABAergic interneurons that hyperpolarize neurons in somatosensory barrel cortex (BC). Optogenetic activation of these neurons switched BC to an adapted mode in which excitatory cells lost their angular tuning. In contrast, however, this was not the case with a general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 81 publications
1
6
0
Order By: Relevance
“…Consistent with this idea, a recent imaging study by Augustininaite & Kuhn (2020) Indeed, considerable literature examining CT circuits describes diverse roles for L6 neurons in modulating sensory transmission. These functions include regulation of gain or excitability (Olsen et al, 2012;Denman and Contreras, 2015;Guo et al, 2017;Wang et al, 2018;Ansorge et al, 2020), sharpening or shifting of sensory response properties (Temereanca and Simons, 2004;Andolina et al, 2007;Li and Ebner, 2007;Hasse and Briggs, 2017;Pauzin and Krieger, 2018;Pauzin et al, 2019;Voigts et al, 2020), enhancement of synchrony (Sillito et al, 1994;Contreras et al, 1996), regulation of sensory adaptation (Mease et al, 2014), and control of burst vs. tonic spiking (Wang et al, 2006;Kirchgessner et al, 2020). The current work complements these studies, and, together, they indicate that L6 CT cells are highly heterogeneous and likely have multiple modulatory functions.…”
Section: Whisking-unresponsive L6 Ct Neuronssupporting
confidence: 66%
“…Consistent with this idea, a recent imaging study by Augustininaite & Kuhn (2020) Indeed, considerable literature examining CT circuits describes diverse roles for L6 neurons in modulating sensory transmission. These functions include regulation of gain or excitability (Olsen et al, 2012;Denman and Contreras, 2015;Guo et al, 2017;Wang et al, 2018;Ansorge et al, 2020), sharpening or shifting of sensory response properties (Temereanca and Simons, 2004;Andolina et al, 2007;Li and Ebner, 2007;Hasse and Briggs, 2017;Pauzin and Krieger, 2018;Pauzin et al, 2019;Voigts et al, 2020), enhancement of synchrony (Sillito et al, 1994;Contreras et al, 1996), regulation of sensory adaptation (Mease et al, 2014), and control of burst vs. tonic spiking (Wang et al, 2006;Kirchgessner et al, 2020). The current work complements these studies, and, together, they indicate that L6 CT cells are highly heterogeneous and likely have multiple modulatory functions.…”
Section: Whisking-unresponsive L6 Ct Neuronssupporting
confidence: 66%
“…As reported previously, sustained periods of local response modulation after laser offset are not observed with photoactivation of other types of corticofugal projection neurons, interneurons, or neuromodulatory inputs. 4,12,23 We were intrigued by the idea that non-auditory inputs could naturally play the role of our laser pulse by recruiting L6 CT neurons to spike shortly before the onset of upcoming acoustic events. We were particularly struck by the nearly perfect coexpression of the forkhead box protein P2 (FoxP2) in cortical Ntsr1-Cre+ neurons, 24,25 a protein that-in mice-is highly enriched in motor control nuclei and distributed brain regions that integrate sensory inputs with motor-related signals.…”
Section: Resultsmentioning
confidence: 99%
“…Analogous approaches that follow the STDP rule were also demonstrated in the auditory (Cruikshank and Weinberger, 2001 ; D’Amour and Froemke, 2015 ) and somatosensory systems (Jacob et al, 2007 ; Litvak et al, 2007 ). However, other in vivo studies revealed a different rule by showing that tuning function was altered only when optogenetic stimulation preceded mechanical whisker stimulation (Khateb et al, 2017 ; Pauzin et al, 2019 ). It is noteworthy that although feature selectivity in single neurons could be modulated (Yao and Dan, 2001 ), the effect of paired stimulation on neuronal populations was reported insignificant in a recent study (Lube et al, 2019 ).…”
Section: Discussionmentioning
confidence: 98%
“…Based on the fact that paired stimulation of excitatory neuron and peripheral sensory inputs could alter feature preference (Meliza and Dan, 2006 ; Jacob et al, 2007 ), we designed an experiment using cell-type-specific optogenetic stimulation and whisker deflection pairs. Optogenetics provides cell-type-specific control, a property that has been utilized to decrease angular tuning in the barrel cortex (Pauzin et al, 2019 ). In the present study, we attempted to test the feasibility of using paired optogenetic and mechanical stimulation to modify the feature selectivity of S1BF neurons in vivo and ascertain the optimal parameters to achieve this goal.…”
Section: Introductionmentioning
confidence: 99%